The higaonon Farm Shifting Cultivation and its Ritual Practices at Rongongon Lanao del Norte - B. TANGIAN, MA. CECILIA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper describes how the local hinterland farmers work for free land tenure but are contained in a defined worldview such as their existing beliefs and external forces. The problem lies on how shifting cultivation provides a means of greater sustainability among the Higaonon in the tribal community of Rogongon since they are governed by the ritual practices that are traditionally bound in their livelihood system. The paper also chronicles the brief origin of Rogongon, the Higaonon Shifting agriculture cycle, the Higanon farm practices that are associated with the supernatural phenomenon and the external forces that are responsible for the continuity and change among the social lives of the tribe. Thus, the researcher employs the use of historical and ethnographic studies in writing about these shifting agricultural processes.